Proceedings of the Joint Symposium on Computational Aesthetics and Sketch-Based Interfaces and Modeling and Non-Photorealistic 2018
DOI: 10.1145/3229147.3229158
|View full text |Cite
|
Sign up to set email alerts
|

Reducing affective responses to surgical images through color manipulation and stylization

Abstract: Original photo of a lasagna dish.Output of HueShift2. Output of FlowAbs [Kyprianidis and Döllner 2008].Figure 1: Two techniques studied in this article, each using a different strategy for making surgery images easier to look at. ABSTRACTWe present the first empirical study on using color manipulation and stylization to make surgery images more palatable. While aversion to such images is natural, it limits many people's ability to satisfy their curiosity, educate themselves, and make informed decisions. We sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 98 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…To better understand the implications of combining a traditional workstation setting with an AR view and how to develop interaction mechanism for such hybrid environments, we conducted a preregistered (https://osf.io/7qegs/) observational study with seven experts in the domain of particle physics. While this number of participants may appear low, it is not an unusually low number when conducting observational studies to understand the needs of domain experts [6,8,28,30,31,47].…”
Section: Observational Studymentioning
confidence: 99%
“…To better understand the implications of combining a traditional workstation setting with an AR view and how to develop interaction mechanism for such hybrid environments, we conducted a preregistered (https://osf.io/7qegs/) observational study with seven experts in the domain of particle physics. While this number of participants may appear low, it is not an unusually low number when conducting observational studies to understand the needs of domain experts [6,8,28,30,31,47].…”
Section: Observational Studymentioning
confidence: 99%
“…Similar findings were reported in a more recent look at studies and participants [65]: in interviews or lab studies (both of which contain qualitative feedback and/or quantitative Likert-scale ratings) the majority of studies are conducted with fewer than 20 participants. In fact, for qualitative feedback and quantitative answers to Likert-scale the average is likely to be even lower and we found that often such research projects report results with 15 or less respondents (e.g., [66][67][68][69][70][71][72]), and sometimes with numbers as low as one (e.g., [68]) or two (e.g., [69]). Finally, we argue based on the literature, that there is no meaningful cut-off point at which a sample size becomes inadequate or invalid because it would be "too small" [73] but instead the relationship between the value of a study and the size of the sample incrementally increases with each additional participant [73].…”
Section: Resultsmentioning
confidence: 97%
“…Similar findings were reported in a more recent look at studies and participants [67]: in interviews or lab studies (both of which contain qualitative feedback and/or quantitative Likert-scale ratings), the majority of studies are conducted with fewer than 20 participants. In fact, for qualitative feedback and quantitative answers to Likert scales, the average is likely to be even lower and we found that often such research projects report results with 15 or less respondents (e.g., [68][69][70][71][72][73][74]), and sometimes with numbers as low as one (e.g., [70]) or two (e.g., [71]).…”
Section: Response Rate and Sample Sizementioning
confidence: 90%